EFEKTIFITAS BEBERAPA JENIS BAHAN ORGANIK TERHADAP PENINGKATAN KESUBURAN TANAH DAN HASIL PADI - Ricky Indri Hapsari; Riyanto Djoko (Universitas Tribhuwana Tunggadewi, 2014)
Rice continuous planting without additional biomass application decreases soil fertility and nutrient stability in the soil. Different kind of legumes crops in the tropic is one of possibility can used an organic fertilizer. The aims of this study was to evaluate legume crops as organic matter, and kind of legume crop potentially has high nutrient in the soil after rice harvest and be continue used by following crops. To evaluate additional organic matters to increased yield of rice. The study was conducted from July to November 2013 at Amadanom village, sub district of Dampit and Malang district. Split plot design was used with three (3) replication and two (2) factor. Main plot consist of N0 (no addition an organic fertilizer), N1 (N an organic fertilizer 30 kg/ha), N2 (N an organic fertilizer 60 kg/ha). Sub plot additional organic matters 20 t/ha consist of : B1 (biomass of Crotalaria juncea L.), B2 (biomass of Sesbania rostrata) and B3 (biomass of Tithonia diversifolia). The result showed that additional biomass Sesbania rostrata and N an organic fertilizer 30 kg/ha increased yield by 104,98%. The high contribution on nutrient content in the soil and application of biomass Sesbania rostrata. It was concluded that organic matter of Sesbania rostrata was effective as organic fertilizer to increased soil fertility and rice yield